Sustained long-term hematopoiesis after myeloablative therapy with peripheral blood progenitor cell support - Haas, Rainer; Witt, Barbara; Möhle, Robert; Goldschmidt, Hartmut; Hohaus, Stefan; Frühauf, Stefan; Wannenmacher, Michael; Hunstein, Werner (Blood, 1995)
A retrospective analysis of long-term hematopoiesis was performed in a group of 145 consecutive patients who had received high-dose therapy with peripheral blood progenitor cell (PBPC) support between May 1985 and December 1993. Twenty-two patients had acute myelogenous leukemia, nine had acute lymphoblastic leukemia, 43 had Hodgkin's disease, 57 had non-Hodgkin's lymphoma, and 14 patients had multiple myeloma. Eighty-four patients were male and 61 female, with a median age of 37 years (range, 16 to 58 years). In 46 patients, PBPC were collected after cytotoxic chemotherapy alone, while 99 patients received cytokines either during steady-state hematopoiesis or post-chemotherapy. Sixty patients were treated with dose-escalated polychemo-therapy, and 85 patients had a conditioning therapy including hyperfractionated total body irradiation at a total dose of 14.4 Gy. The duration of severe pancytopenia posttransplantation was inversely related to the number of reinfused granulocyte-macrophage colony-forming units (CFU-GM) and CD34+ cells. Threshold quantities of 2.5 × 106 CD34+ cells per kilogram or 12.0 × 104 CFU-GM per kilogram became evident and were associated with rapid neutrophil and platelet recovery within less than 18 and 14 days, respectively. These numbers were also predictive for long-term reconstitution, indicating that normal blood counts are likely to be achieved within less than 10 months after transplantation. Conversely, 12 patients were autografted with a median of 1.75 × 104 CFU-GM per kilogram resulting in delayed recovery to platelet counts of greater than 150 × 109/L between 1 and 6 years. Our study includes bone marrow examinations in 50 patients performed at a median follow-up time of 10 months (range, 1 to 85 months) posttransplantation. A comparison with normal volunteers showed a 3.2-fold smaller proportion of bone marrow CD34+ cells, which was paralleled by an even more pronounced reduction in the plating efficiency of CFU-GM and burst-forming unit-ery-throid. No secondary graft failure was observed, even in patients autografted with relatively low numbers of progenitor cells. This suggests that either the pretransplant regimens were not myeloablative, allowing autochthonous recovery, or that a small number of cells capable of perpetual self-renewal were included in the autograft products.
Elektronische Reproduktion der Druck-Ausgabe 21. Dezember 2020
Gesehen am 19.05.2025